Pengaruh Competitor Accounting Terhadap Kinerja Organisasi Melalui Keunggulan Bersaing Sebagai Variabel Intervening - Rosfyan, Ummi Awalia; Samsiah, Siti; Nurfitriana (Jurnal Ilmiah Raflesia Akuntansi, 2024)
Entrepreneurs can use competitor accounting as a strategy to achieve competitive advantage along with optimizing organizational performance in the fishing tackle business in Pekanbaru. The population in this study was 82 fishing businesses registered on kemenkopukm.com. The sampling technique in this research is a saturated sample. The number of samples is the same as the population because the number of samples is small. Data analysis used SEM PLS with software Warp PLS 7.0. It can be concluded that competitor accounting has a affects on competitive advantage and organizational performance, competitive advantage has a affects on organizational performance, while competitor accounting has no effect on organizational performance through competitive advantage as an intervening variable.